Respuesta :

Answer:

y = (12-2x)/3

Step-by-step explanation:

Isolate the variable by subtracting -2x and dividing by 3

Answer:
y = 2(6 - x)/ 3
*ps. I attached an image of what it should look like when you write it

Explanation:
Step 1 - Subtract 2x from both sides of the equation

2x + 3y = 12
2x - 2x + 3y = 12 - 2x
3y = 12 - 2x

Step 2 - Divide both sides of the equation by 3

3y = 12 - 2x
3y/ 3 = 12 - 2x/ 3
y = 12 - 2x/ 3

Step 3 - Factor

y = 12 - 2x/ 3
y = 2(6 - x)/ 3
Ver imagen therobin